The Association of Albuminuria With Tubular Reabsorption of Uric Acid: Results From a General Population Cohort. Issue 2 (25th April 2014) - Scheven, Lieneke; Joosten, Michel M.; de Jong, Paul E.; Bakker, Stephan J. L.; Gansevoort, Ron T.; ,
Abstract : Background: Elevated albuminuria as well as an increased serum uric acid concentration is associated with poor cardiovascular outcome. We questioned whether these 2 variables (albuminuria and serum uric concentration) may be interrelated via tubular uric acid reabsorption. Methods and Results: Included were 7688 participants of the PREVEND Study, an observational, general population‐based cohort study. Linear regression analyses were used to test associations of baseline albuminuria with baseline serum uric acid concentration and tubular uric acid reabsorption (calculated as [100−fractional uric acid excretion]%). Cox regression analyses were used to study the association of baseline serum uric acid and albuminuria with incident cardiovascular morbidity and mortality. In cross‐sectional analyses, albuminuria was associated positively with serum uric acid concentration, both crude and after adjustment for potential confounders (both P <0.001). Albuminuria was found to be associated positively with tubular uric acid reabsorption, again both crude and after adjustment for potential confounders (both P <0.001). In longitudinal analyses during a median follow‐up of 10.5 years, 702 cardiovascular events occurred. After adjusting for cardiovascular risk factors, both albuminuria and serum uric acid were associated with incident cardiovascular events (Hazard Ratios 1.09 [1.03 to 1.17], P =0.01 and 1.19 [1.09 to 1.30], P <0.001, respectively). A significant interaction between these variables was present ( P <0.001), consistent with high serum uric acid being less predictive for cardiovascular morbidity and mortality in the presence of high albuminuria and vice versa. Conclusions: Albuminuria is strongly associated with tubular uric acid reabsorption, and consequently with serum uric acid concentration. This phenomenon may explain in part why albuminuria is associated with cardiovascular outcome.